Representative body of local government: effects and costs of business presence - Vitkovskaya, T.B. (Perm Federal Research Centre Journal, 2018)
The article examines effects that presence of business in deputy corps and use of deputy (political) status in business activity have on potential of representative body of local government. The article is based on an empirical study of power in two Russian small towns - Kushva, Sverdlovsk region and Kungur, Perm region. Motives of entrepreneurs elected as deputies are presented. It is shown how the specificity of their interests affects the agenda of the representative body of public authority. The research specifies peculiarities of functioning of local government bodies in which local business is widely represented. It is shown how this type of representative bodies promotes rise of informal practices of authority and business interaction in the space of a town. It is proved that representative bodies of local government could act as coordinating and communicative platforms or lobbying platforms for local politicians and entrepreneurs. Conclusion is made about limited possibilities of realizing political potential of representative bodies of local government that are mainly comprised of local business